2012
DOI: 10.1155/2012/847246
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hypothalamic Inflammation Associated with the Susceptibility to Obesity in Rats Exposed to High-Fat Diet

Abstract: Inflammation has been implicated in the hypothalamic leptin and insulin resistance resulting defective food intake during high fat diet period. To investigate hypothalamic inflammation in dietary induced obesity (DIO) and obesity resistant (DIO-R) rats, we established rat models of DIO and DIO-R by feeding high fat diet for 10 weeks. Then we switched half of DIO and DIO-R rats to chow food and the other half to high fat diet for the following 8 weeks to explore hypothalamic inflammation response to the low fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
61
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 37 publications
8
61
1
1
Order By: Relevance
“…In the current study we found glucose and sucrose increased TNF-α mRNA expression. This effect is similar to that caused by high fat diet [30]. By contrast HFCS and fructose had no significant effect on TNF-α expression.…”
Section: Discussionsupporting
confidence: 77%
“…In the current study we found glucose and sucrose increased TNF-α mRNA expression. This effect is similar to that caused by high fat diet [30]. By contrast HFCS and fructose had no significant effect on TNF-α expression.…”
Section: Discussionsupporting
confidence: 77%
“…Wang suggests that once animals that have been made obese with a high fat diet are switched to a chow diet, the resulting elevated TNF expression does not return to levels of control (62). The importance of this finding here is that even if these animals were removed from the sugar diet they may still suffer from elevations of this inflammatory peptide.…”
Section: Tumor Necrosis Factormentioning
confidence: 83%
“…After the switch to a regular chow diet however, the upregulation of these TNF did not return to normal. This suggests that it may not be possible to reduce the inflammatory response that results from obesity (62). This is an important finding that may impact the way obesity therapies are designed.…”
Section: Tumor Necrosis Factormentioning
confidence: 99%
“…Eating high fat chow also increases inflammation, both in adipose tissue and in the hypothalamus (Thaler et al, 2012; Wang et al, 2012). For example, the proinflammatory cytokines tumor necrosis factor (TNF)-alpha and interleukin (IL)-6 are significantly increased in hypothalamic tissue from rats eating high fat chow (Maric et al, 2014; Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%